Surveillance of human leptospirosis infections in Ukraine between 2018 and 2023 - Petakh, Pavlo; Tymchyk, Viktoriia; Kamyshnyi, Oleksandr (Frontiers in Public Health, 2024)
Leptospirosis is a bacterial disease that affects both humans and animals worldwide. Currently, a positional war is ongoing in Ukraine, and the military is encountering a significant number of rodents in trenches and dugouts, which are known reservoirs for Leptospira, the causative agent of leptospirosis a potentially dangerous infectious disease with a high mortality rate. The civilian population is also at potential risk of leptospirosis. The destruction of the Kakhovka Dam on June 6, 2023, has led to widespread devastation and human suffering. In the short term, there is a significant risk of rodentborne diseases such as leptospirosis.We utilized data from the Ukrainian Centre for Disease Prevention Control and observed a substantial increase in prevalence in 2023. The notification rate in Ukraine in 2023 was 1.06 per 100,000 persons, which is higher than that of other countries in the European Union. Particular attention is being given to Zakarpattia Oblast, located on the western border of Ukraine, which shares boundaries with Romania, Hungary, Poland, and Slovakia, with an extremely high incidence rate of 12.08 per 100,000 persons. Based on these findings, we recommend education and awareness campaigns, vaccination, personal protective measures, and improved surveillance to address the increasing incidence of leptospirosis in Ukraine.